Enhancing Qur’anic Memorization through the Yanbu’a Method: The Role of Tahfidz Teachers at SD Takhassus Al-Qur’an Walisanga Tanjung - Moh. Abd Faiz; Solekhul Amin; Eka Novita Sari; Vina Maulida Fitria (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study, titled “The Role of Tahfidz Teachers in Improving Memorization through the Yanbu'a Method at SD Takhassus Al Qur'an Walisanga Tanjung,” aims to determine the role of tahfidz teachers in improving students' memorization of juz 'amma using the yanbu'a method at SD Takhassus Al Qur'an Walisanga Tanjung ’an Walisanga Tanjung, as well as to identify the supporting factors and obstacles faced by hafiz teachers in improving students’ memorization. The research method used by the author involved data collection through interviews, observations, and documentation, resulting in qualitative data. The research findings regarding the role of hafiz teachers in improving students' memorization of Juz ‘Amma include: 1) as educators who apply learning methods according to students’ varying abilities, 2) as managers who ensure the orderly conduct of the learning process, 3) as administrators who use a system for documenting daily and semester achievements, 4) as supervisors who use face-to-face techniques to monitor students' memorization, 5) as a leader through structured time allocation (30 minutes of musyafahah, 30 minutes of ardul qiro’ah), 6) as an innovator by conducting ice-breaking activities and adjusting the pace of learning, and seventh, as a motivator through inspirational stories of Quran memorizers. Therefore, the findings of this study, namely the role of tahfidz teachers in improving students' memorization of Juz 'Amma using the Yanbu'a method, have proven to be effective through structured strategies and repetition